2002
DOI: 10.1007/s00296-001-0165-8
|View full text |Cite
|
Sign up to set email alerts
|

The CD14+ CD16+ monocyte subset in rheumatoid arthritis and systemic lupus erythematosus

Abstract: Most human peripheral blood monocytes strongly express surface CD14, but not CD16 (CD14+ +/CD 16-). A smaller group of monocytes express lower levels of CD14 and also express CD16 (CD14+/CD16+). This subgroup has different functional characteristics and is expanded in a number of disease states. We aimed to determine the percentage of circulating CD14+ /CD16+ monocytes in rheumatoid arthritis and systemic lupus erythematosus (SLE) and relate this to disease measures. Peripheral blood was sampled from 31 SLE pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 14 publications
7
42
1
1
Order By: Relevance
“…Similar proportions of monocyte subsets in both SLE patients and healthy controls have been previously reported (4,5,26). In contrast, one study demonstrated that patients with inactive SLE without immunosuppressive therapy had increased numbers and percentages of CD14ϩCD16ϩ monocytes as compared with patients with active SLE and healthy controls.…”
Section: Discussionmentioning
confidence: 69%
“…Similar proportions of monocyte subsets in both SLE patients and healthy controls have been previously reported (4,5,26). In contrast, one study demonstrated that patients with inactive SLE without immunosuppressive therapy had increased numbers and percentages of CD14ϩCD16ϩ monocytes as compared with patients with active SLE and healthy controls.…”
Section: Discussionmentioning
confidence: 69%
“…However, the relevance of these changes to the increased numbers of macrophages in RA synovium discussed above remains to be established. Peripheral blood monocyte subsets have recently been identified (43)(44)(45) and, for reasons that are unclear, conflicting observations of their ratios have been reported in RA patients, with different studies showing an increased or reduced proportion of the CD14 low CD16ϩ subset (46,47). The potential significance of these subsets is detailed below.…”
Section: Mechanisms Controlling Ra Synovial Macrophage Numbersmentioning
confidence: 99%
“…In humans, 2 main monocyte populations have been delineated, namely, the major CD14ϩCD16Ϫ and the minor CD14 low CD16ϩ subsets (43). As mentioned above, there have been conflicting findings regarding the ratio of these subpopulations in the blood of RA patients (46,47). The CD14ϩCD16Ϫ subpopulation is considered to be the less mature, while the more mature CD14 low CD16ϩ monocytes have been called "inflammatory" monocytes (44,134), in part because their level may be elevated in blood in inflammatory conditions, such as RA (135), and in part because they produce TNF in response to LPS (44,134).…”
Section: Macrophage Lineage Heterogeneitymentioning
confidence: 99%
“…Of note, CD14 + CD16 + monocytes expressing low or high levels of CD14 seem to develop into dendritic cells or macrophages, respectively (16). In addition, several studies reported an increased number of circulating CD14 + CD16 + in the course of infections, inflammation, and malignant diseases (17)(18)(19)(20). Another subpopulation of circulating monocytes expresses the CD2 marker and these cells have been described as dendritic cells (21,22).…”
Section: Introductionmentioning
confidence: 99%